2010
DOI: 10.1007/s00383-010-2689-z
|View full text |Cite
|
Sign up to set email alerts
|

Crohn’s disease limited to the appendix: a case report in a pediatric patient

Abstract: In the original description of Crohn's disease, the appendix was not believed to be involved in the inflammatory process. Later on, case reports started to appear in publications demonstrating that the appendix could be involved in the inflammatory changes of Crohn's disease, and it could also be the primary or the sole manifestation of the disease. Being that appendectomies are one of the most common procedures performed by pediatric surgeons, the knowledge about this diagnosis, all be it rare, is important. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Furthermore, the initial presentation of pediatric CD may resemble acute appendicitis. [456] Although the intraoperative findings in our patient with ileocecal CD suggested inflammation of the appendix with local peritonitis, the histological investigation confirmed only periappendicular inflammation without involvement of the appendix. The periappendicular inflammation and the pus were probably due to extension of the inflammatory process from the microperforation of the terminal ileum.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, the initial presentation of pediatric CD may resemble acute appendicitis. [456] Although the intraoperative findings in our patient with ileocecal CD suggested inflammation of the appendix with local peritonitis, the histological investigation confirmed only periappendicular inflammation without involvement of the appendix. The periappendicular inflammation and the pus were probably due to extension of the inflammatory process from the microperforation of the terminal ileum.…”
Section: Discussionmentioning
confidence: 70%
“…The concept of Crohn’s disease limited to the appendix was once generally accepted, on the basis of the histological resemblance of some cases of granulomatous appendicitis to Crohn’s disease. However, the clinical presentation was often acute or subacute abdominal pain, and these patients did not present with long‐term symptoms of Crohn’s disease . More significantly, whereas Crohn’s disease often recurs after surgical resection of a diseased segment of intestine, patients with Crohn’s‐like appendicitis develop Crohn’s disease in other intestinal segments in <10% of cases …”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical presentation was often acute or subacute abdominal pain, and these patients did not present with long-term symptoms of Crohn's disease. [4][5][6] More significantly, whereas Crohn's disease often recurs after surgical resection of a diseased segment of intestine, patients with Crohn's-like appendicitis develop Crohn's disease in other intestinal segments in <10% of cases. 7,8 The differential diagnosis of Crohn's-like appendicitis or granulomatous appendicitis includes several infections, although some, such as tuberculosis or parasitic infection, are uncommon in Western populations.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, these reports have concluded that compared to antibiotics-only groups, surgical therapy results in a significantly higher efficacy rate at 1 year, equivalent length of hospital stay, sick leave, and post-hospital symptom duration, and has been recommended as the definitive treatment of acute appendicitis [12], [14], [15]. While laparotomy with washout and appendectomy has been the standard of care for the surgical management of perforated hernial appendicitis, [16]; more recent reports describe the safety and advantages to laparoscopy [9]. The laparoscopic approach proved beneficial for our patient, as it simultaneously allowed excellent visualization of her intra-abdominal contents, including the viability of the bowel within and on ingress into the hernia sac, reduction of the hernial contents, comprehensive peritoneal washout, and appendectomy, without incurring the additional morbidity of a large herniotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve to 16% of patients with Crohn’s disease who have ileal involvement and 20–50% with colonic involvement present with the inflammatory process extending to the appendix [18], [19]. About 85% of patients with appendiceal Crohn’s present with acute abdominal pain in the right iliac fossa, similar to classic appendicitis symptoms [5], [16].…”
Section: Discussionmentioning
confidence: 99%